Discipline Body and Digital Panopticism to Woman Instagram Influencer through Hijab Discourse - Ardilla, Yunda Presti; Agustin, Sari Monik (Mediator: Jurnal Komunikasi, 2024)
In contemporary society, the migration of interactions among millennials, particularly Muslim women serving as influencers, to digital platforms has spurred an intriguing shift. However, this transition is fraught with complexities as these women encounter digital media panopticism, constraining their liberty of expression. This study delves into the propagation of hijab discourse within millennial influencer circles via digital channels, aiming to unveil the established truths propagated by authoritative figures. Employing Foucault’s notion of panopticism, discursive practices, and Howe-Strauss’ Millennial generation, this research employs critical constructionism, qualitative methodologies, and in-depth interviews to unravel the pervasive digital panopticism shaping the disciplined digital personas of these influencers. The investigation uncovers how authorities utilize digital panopticism to regulate influencers, aligning with Foucault’s theories. This discreet strategy amplifies influence while perpetuating continuous surveillance through participatory transparency. By penalizing deviations from the hijab discourse, authorities instill fear, prompting self-discipline on social media platforms. Despite influencers’ vigilance, the opaque nature of control fosters ambiguity, highlighting the subtle yet profound impact of power dynamics in digital spaces. This observation echoes Foucault’s discourse on subtle regulatory mechanisms in contemporary society, underscoring the pervasive influence of power dynamics in digital spheres.